Single-center experience with the ClotTriever BOLD catheter for deep vein thrombosis percutaneous mechanical thrombectomy of the lower extremity - De Marco Garcia, Lorena P. (Frontiers in Surgery, 2023)
The ClotTriever System is a percutaneous mechanical thrombectomy system used to treat deep vein thrombosis (DVT). The BOLD catheter is a newer compatible component with a modified coring element for which exerts greater radial force for improved venous wall apposition and removal of organized or wall-adherent thrombus. Reported outcomes with the BOLD catheter are limited, and considering the more robust design, this. This retrospective study aimed to assess the preliminary procedural safety and success data for patients treated with the BOLD catheter. Methods: Consecutive patients with symptomatic lower extremity DVT who underwent thrombectomy with the BOLD catheter between November 23, 2021-June 26, 2022, at a single center were included. Baseline and procedural characteristics are reported. The primary outcome, intraprocedural safety, was assessed by chart review of recorded intraprocedural adverse events (AEs) or device malfunction. The secondary outcome, procedural success, was defined as ≥75% reduction in the total occlusion across iliofemoral treated venous segments. This was assessed by interventionalist review of pre-and post-procedural venograms. Results: Eleven patient cases were reviewed. Median patient age was 65 years, the majority were female, and all were treated unilaterally. All procedures were completed in a single session without intraprocedural AEs or device malfunction. The median procedural blood loss was 50 mL. Review of pre-and post-procedural venograms showed a total of 35 iliofemoral venous segments were treated, including the femoral (n=9), common femoral (n=9), external iliac (n=10), and common iliac (n=7) veins. Procedural success was achieved in 10 patients (90.9%) and the median reduction in venous occlusion was 100%. The median length of postprocedural hospital stay was 1 day and there were no AEs through discharge (N=11). One adverse event occurred among the 8 patients who completed their follow-up visit. A patient with advanced-stage cancer and medication failure had a recurrent DVT 13 days post procedure which was not related to the device or procedure. Conclusion: No safety concerns with the BOLD catheter were raised during review of the cases included in this analysis and the device was effective successful in reducing venous occlusion in patients with symptomatic proximal lower extremity DVT.